Ion-exchange HPLC-ICP-MS: A new window to chromium speciation in biological tissues - Pechancová, Radka; Gallo, Jiří; Milde, David; Pluháček, Tomáš (Talanta, 2020)
The presented work proposes a novel analytical ICP-MS-based approach for the accurate and precise chromium speciation in biological tissues. The determination of total Cr(VI) and soluble Cr(III) species was carried out by alkaline EDTA extraction followed by their separation using ion-exchange high-performance liquid chromatography inductively coupled plasma mass spectrometry (IE-HPLC-ICP-MS). The developed method was validated according to the procedure given in the United States Food and Drug Administration guideline on the validation of bioanalytical methods. Validation parameters included limit of detection (≤ 0.03 μg g-1), limit of quantification (≤ 0.08 μg g-1), linearity (r ≥ 0.9998), intra-day and inter-day accuracy (86-110%) and precision (≤ 10%), extraction recovery (89-110%), carry-over effect and sensitivity. In addition, special attention was paid to the study of chromium species interconversion and the elimination of spectral interferences. Moreover, the validated ICP-MS method employing microwave acid digestion was used to determine the total Cr content in collected fractions. Finally, the whole ICP-MS-based methodology was applied to the analyses of two certified reference materials of hepatopancreas tissue. Obtained results indicated that the majority of chromium in biological tissues is bound to the solid residue, Cr(VI) was determined in none of the samples investigated. This is the first study focusing on soluble Cr(III), total Cr(VI), and total bound Cr species in biological tissues. It is characterized by efficient sample preparation and fast simultaneous analysis of Cr species with parallel total Cr analysis serving for chromium balance evaluation.
Keywords: Chromatography, High Pressure Liquid; Chromium; Spectrum Analysis; Speciation analysis; vysokoúčinná kapalinová chromatografie; ICP-MS; Mass Spectrometry; HPLC; Chromatography, Ion Exchange; hmotnostní spektrometrie; chrom; Biological tissues; chromatografie iontoměničová; spektrální analýza